2020
DOI: 10.1016/j.sleep.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep disturbances during COVID-19 outbreak in an urban Chinese population: a cross-sectional study

Abstract: Objective The COVID-19 pandemic is a large-scale public health emergency that likely precipitated sleep disturbances in the community. This study aimed to investigate the prevalence and correlates of sleep disturbances during the early phase of COVID-19 pandemic. Methods This web-based cross-sectional study recruited 1138 Hong Kong adults using convenience sampling over a two-week period from 6th April 2020. The survey collected data on sleep disturbances, mood, stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 31 publications
7
64
3
5
Order By: Relevance
“…Our data are in agreement with other Chinese surveys in adolescents and young adults, reporting an increase in the prevalence of insomnia symptoms during the COVID-19 epidemic period[ 24 , 25 ] and also with other studies carried-out in Asia and Europe that showed sleep disturbances in up to a third of their samples[ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in agreement with other Chinese surveys in adolescents and young adults, reporting an increase in the prevalence of insomnia symptoms during the COVID-19 epidemic period[ 24 , 25 ] and also with other studies carried-out in Asia and Europe that showed sleep disturbances in up to a third of their samples[ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, cross-sectional studies have found 30-70% of adults to report poor or insufficient sleep during the COVID-19 pandemic. [9][10][11][12][13] However, there have also been some indications of improvements in sleep, with studies finding adults to have longer sleep duration during COVID-19 5,8 and for a higher percentage to obtain the recommended amounts of nighttime sleep. 5 Similarly, a qualitative study with 45 adolescents found adolescents to report a delayed sleep schedule (by about two hours), improved sleep quality, longer sleep duration, and less daytime sleepiness during COVID-19 compared to before COVID-19.…”
Section: Covid-19mentioning
confidence: 99%
“…Based on research suggesting increased sleep duration during COVID-19 in non-ADHD samples, 5,8 but not in youth with ADHD, 30 it was also hypothesized that adolescents with ADHD would be less likely than adolescents without ADHD to obtain recommended sleep duration during the pandemic. Also based on extant studies with adults, [9][10][11][12][13] we expected higher rates of clinically-elevated difficulties initiating and maintaining sleep during the pandemic compared to before the pandemic, particularly for adolescents without ADHD relative to adolescents with ADHD. 29 2.…”
Section: Adhdmentioning
confidence: 99%
“…The questionnaire was collected through social media WeChat (15) (Tencent, Shenzhen, China) using an online survey platform Sojump (Changsha ran Xing InfoTech Ltd.,) during February 6th to 13th, 2020, when the epidemic was in the outbreak period, the situation was chaotic (16)(17)(18) and the number of people infected with COVID-19 was escalating. The convenience sampling was adopted.…”
Section: Data Collectionmentioning
confidence: 99%